“You’re young, intelligent, and beautiful”: How Microaffirmations Inspire Summer Bridge Program Students to Persist - Makeda K. Turner; James M. Ellis; Janella D. Benson; Carmen N. McCallum (Journal of Postsecondary Student Success)
Research shows that Summer Bridge Programs (SBPs) are essential in supporting undergraduate students’ first-year college transition experiences from underrepresented and historically marginalized backgrounds. A key component of SBPs is cultivating deeply supportive relationships participants establish with adults and peers on a college campus. The academic and social support participants receive from these relationships is beneficial and critical for navigating microaggressions they may experience on campus. However, how these affirming and deeply supportive relationships are formed within SBPs is an underexplored phenomenon in the literature. This qualitative study, focusing on the role of microaffirmations, describes and explores how a SBP cultivated an environment that enabled participants to develop supportive relationships to aid their first-year transition on a college campus. Findings indicate that racial microaffirmations in the form of personalized support from peer advisors and adults and cultivating confidence to engage academically and socially on campus were vital in assisting program participants with their first-year college transition. Implications of these findings are discussed.